Effect of hydroxypr1opylation on physical properties, antifungal and mycotoxin inhibitory activities of clove oil emulsions coated with chitosan. (December 2022) - Liu, Hua; Chu, Beibei; Li, Jiangyang; Li, Wenzhe; Wu, Dianhui; Lu, Jian; Chen, Xingguang
Abstract: Fusarium graminearum is one of the most common fungi infecting grains and the production of mycotoxin, deoxynivalenol (DON), poses a serious threat to human and livestock health. Chitosan coated emulsion can be used as a highly effective antifungal agent. However, the poor solubility of chitosan leads to a longer ultrasonic time for preparing emulsion. In our work, hydroxypropyl chitosan with better water dispersion was prepared and used as a coating for clove oil emulsion, and the effect of hydroxypropylation on the physical properties, antifungal and mycotoxin inhibitory activities of chitosan coated clove oil emulsion was investigated. Compared with unmodified chitosan coated clove oil emulsion, hydroxypropyl chitosan coated clove oil emulsion had smaller particle size, lower viscosity, and its maximum reduction of the mycelial diameter and the minimum fungicidal concentration was 35% and 50%, respectively. These results indicated that hydroxypropylation could improve the physical properties and antifungal activity of chitosan coated clove oil emulsion to a certain extent. Surprisingly, after being cultured in barley medium for 7 d, the maximum reduction of DON and ergosterol accumulation was 87% and 86% respectively, showing that hydroxypropyl chitosan coated clove oil emulsion can inhibit the production of DON by mitigating the growth of F. graminearum. Moreover, clove oil emulsions coated with high molecular weight hydroxypropyl chitosan showed a stronger inhibitory effect on the accumulation of DON and ergosterol. This work can provide a reference for mitigating fungal growth and mycotoxin production in food by essential oil emulsions. Graphical abstract: Image 1 Highlights: Hydroxypropyl chitosan was first used to coat clove oil emulsion. Hydroxypropylation reduced the particle size of emulsions coated with chitosan. Hydroxypropylation decreased the rheological viscosity of emulsions coated with chitosan. Hydroxypropylation improved the antifungal and mycotoxin inhibitory ability of emulsions coated with chitosan.